2015
DOI: 10.2147/dmso.s80907
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting high-sensitivity cardiac troponin T elevation in Japanese metabolic syndrome patients

Abstract: PurposeThe blood concentration of cardiac troponin T (ie, high-sensitivity cardiac troponin T [hs-cTnT]), measured using a highly sensitive assay, represents a useful biomarker for evaluating the pathogenesis of heart failure or predicting cardiovascular events. However, little is known about the clinical significance of hs-cTnT in metabolic syndrome. The aim of this study was to examine the factors affecting hs-cTnT elevation in Japanese metabolic syndrome patients.Patients and methodsWe enrolled 258 metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…In previous cross-sectional studies, CAVI is associated with various cardiovascular risk factors. CAVI correlates with high-sensitivity cardiac troponin T [116], renal function [117], non-dipper type hypertension [118], hyperuricemia [119], dyslipidemia [120], coronary calcium [121,122], polyneuropathy in type 2 diabetics [123], paroxysmal atrial fibrillation [124], carotid intima-media [125,126,127,128], and lacunar silent cerebral infarction in patients with atrial fibrillation [129]. In addition, CAVI correlates with skin autofluorescence, which evaluates deposition of advanced glycation end products by detecting light intensity per nanometer between 300 and 420 nm in patients with type 2 diabetes mellitus [130].…”
Section: Cavi and Cardiovascular Risk Factorsmentioning
confidence: 99%
“…In previous cross-sectional studies, CAVI is associated with various cardiovascular risk factors. CAVI correlates with high-sensitivity cardiac troponin T [116], renal function [117], non-dipper type hypertension [118], hyperuricemia [119], dyslipidemia [120], coronary calcium [121,122], polyneuropathy in type 2 diabetics [123], paroxysmal atrial fibrillation [124], carotid intima-media [125,126,127,128], and lacunar silent cerebral infarction in patients with atrial fibrillation [129]. In addition, CAVI correlates with skin autofluorescence, which evaluates deposition of advanced glycation end products by detecting light intensity per nanometer between 300 and 420 nm in patients with type 2 diabetes mellitus [130].…”
Section: Cavi and Cardiovascular Risk Factorsmentioning
confidence: 99%
“…7 An association between cTnT and N-terminal pro-B-type natriuretic peptide (NT-proBNP) was reported in individuals with the metabolic syndrome. 8 In Black men from the Sympathetic activity and Ambulatory Blood Pressure in Africans (SABPA) cohort, cTnT was also associated with NT-proBNP, which may indicate increased cardiac wall strain in our population group. 9 There is increasing evidence to suggest a role of cardiac stress in the development of neurodegenerative diseases as cTnT and NT-proBNP are independently associated with cognitive decline.…”
Section: Prospective Associations Between Cardiac Stress Glucose Dysmentioning
confidence: 78%
“…Sato et al also reported that age, eGFR, and Cornell voltage were significantly associated with hs-cTnT based on multivariate analysis. In addition, other clinical reports indicated a significant relationship between BNP and hs-cTnT [ 1 , 23 ]. The analysis in this study also selected these factors as independent variables for hs-cTnT as a subordinate factor.…”
Section: Discussionmentioning
confidence: 99%